(untitled) (KASBIT Business Journal, 2022)
This study investigates the role of trust in a leader in the relationship between the dimensions of job satisfaction and transformational leadership in the banks of Karachi. The study employs a quantitative methodology where data is collected at three equal intervals to escape the common method bias. In first month, 250 questionnaires were distributed to those employees working in a bank who had the same supervisor for the last six months to measure the leadership style returned 239. A second time after a month, questionnaires were distributed to 239 respondents who previously filled the questionnaire to measure trust in a leader returned 227. Lastly, after one more month, the 227 questionnaires were distributed, and returned were 215. In this study structural model technique is used by using Amos software. The results indicate that trust is mediating the relationship between three transformational leadership dimensions (Individualized Consideration, Inspirational Motivation, Intellectual Stimulation) and job satisfaction. Hence, trust mediates the relationship between job satisfaction and transformational leadership dimensions. Findings show that managers in the banking industry of Karachi should focus on providing individualized consideration and intellectual stimulation to increase satisfaction on job as these two elements significantly impact the satisfaction on job of the banking industry employees of Karachi. They can also work on inspirational motivation by building their employees’ trust in them as trust in leaders signifies the relation between inspirational motivation and job satisfaction.